Computer says no: technology and accountability in policing traffic stops - Kinsella, Clare (Crime, law and social change, 2011)
The Road Traffic Act 1988 gives police in the United Kingdom the power to seize motor vehicles which they have reasonable grounds for believing are being driven without a valid driver’s licence or motor insurance. Drivers may then have to pay a fee to have their vehicles returned. When exercising this power of seizure, the police may rely on information contained on the Police National Computer (PNC) which is linked to the National Insurance Database (NID). Whilst these databases are undoubtedly invaluable in this endeavour, they are not always accurate, and incidents have occurred whereby motorists who are in fact driving with valid insurance have had their vehicles seized and retained. Focusing on the case of Lisa, whose vehicle was wrongly impounded by Merseyside Police in 2007, and other cases, we explore the legitimacy and legality of such activity. We question both the discretionary power of the police in taking such action, and the validity of their (over) reliance on technology. We posit that the taking of money in cases such as Lisa’s is evidence of the turn within public policing towards marketisation, and consider the capacity for harm to innocent individuals and the implications for justice and fairness. Ultimately, we contend that police accountability is compromised and that a new approach is required. We close the piece with some recommendations for improved police practice.